Sense of Control and Safety Compliance in the Prevention of COVID-19: A Framework Based on Conservation of Resources Theory - Li, Pingping; Zhu, Huaixin (Frontiers in Psychology, 2022)
Drawing on conservation of resources theory, this study examined how and when sense of control influence safety behavior (e.g., safety compliance and safety participation). Linear regression analysis was performed on data collected from 481 students in 58 classes at a university. The results indicated that psychological stress mediated the negative effect of sense of control on safety compliance, as well as the positive effect of sense of control on safety participation. They further showed that perceptions of stronger safety regulations heightened the positive relationship between student psychological stress and safety compliance, and buffered the negative effects of psychological stress on safety participation. These results provide a benchmark against which the effectiveness and relevance of epidemic prevention and control in higher education institutions can be assessed.